ANALISIS YURIDIS TENTANG MAL ADMINISTRASI KANTOR NOTARIS DITINJAU BERDASARKAN PASAL 16 UU NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - JULI MURNIATY GINTING (PREMISE LAW JURNAL, 2015)
The making of a Notarial Administrative Mal sometimes is not in line with the provision in Article 16 of UUJN (Notarial Act) such as not reading the content of a deed, being biased, working outside the working area, signing not before a Notary, lowering the fee in order to get a lot of profit, cooperating with agents or corporate body as a middleman in finding clients, owning more than one office, either branch office or representative office, and embezzling tax return. The research used descriptive analytic and judicial normative approaches. The data were gathered by conducting library research and field study deductively which was related to the mechanism of notarial administrative mal according to Article 16 of UUJN. The mechanism of notarial administrative mal is made to anticipate various problems in the future. The criminal sanction occurs when the Notary’s action is fatal and can harm other people. He is charged with counterfeiting document(s) which, according to Law, can be imprisoned or charged with indemnity. Keywords: Notarial Administrative Mal